Effects of chromium propionate and supplemental amino acids on dairy cattle performance near peak lactation - Vargas, Francisco J.; Yuan, Kai; Titgemeyer, Evan C.; Mamedova, Laman; Bradford, Barry J. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2014)
Feeding chromium in early lactation can increase milk production, but responses during peak lactation have not been studied. The objective of this study was to evaluate responses to chromium propionate during this period as well as interactions with rumen-protected lysine and methionine. Chromium propionate increased feed intake and tended to increase energy-corrected milk yield, and primiparous cows showed greater responses in feed intake and milk protein yield than multiparous cows. In this study, feeding chromium propionate near peak lactation increased feed intake and tended to increase productivity, but no benefits of supplementing rumen-protected lysine and methionine were observed.
Dairy Research, 2013 is known as Dairy Day, 2013
Keywords: Chromium; Amino acids; Lactation